JAMALUDDIN AL-AFGHANI'S POLITICAL RENEWAL THOUGHTS & THEIR RELEVANCE TO 21ST CENTURY ISLAMIC CIVILIZATION - Muhammad Rasyid Ridlo; Syarifudin, Ahmad (International Journal of Multidisciplinary Reseach, 2025)
This research aims to see, explore, and relate Jamaluddin al-Afghani's political thought that developed in the 19th century to the 21st-century Islamic civilization. The main focus of this research is to see al-Afghani's contribution in facing the decline of Islamic civilization caused by internal and external sides. The internal side such as Muslim rulers who are not competent in their duties and the external side is the challenge of modernity such as Western misperceptions of Muslims, sectarianism, and dependence on the West. Using qualitative research methods, this research explores the meaning, concept, and understanding of history so that it can be understood scientifically with a descriptive-narrative presentation. The data source used is library research. The findings of this study reveal that al-Afghani's advocacy for the revival of Islamic civilization remains relevant to this day. Although there are differences in context between al-Afghani's lifetime and the present, the fundamental principles underlying his thinking remain relevant. Such as reconciling religious thought and rationality, the unity of Muslims or in al-Aghani's language referred to as Pan-Islamism, and the concept of a state based on religion. So based on this thinking, Muslims in the 21st century can map out a more contextual strategy by facing today's challenges.